Progress, Challenges, and Prospects of Soft Robotics for Space Applications. (30th June 2022) - Zhang, Yongchang; Li, Pengchun; Quan, Jiale; Li, Longqiu; Zhang, Guangyu; Zhou, Dekai
Abstract : The development of space robots is vital to broadening human cognitive boundaries. Space robots have been deployed in space science experiments, extravehicular operations, and deep space exploration. The application of space robots undoubtedly reduces the risk and cost of space activities. Traditional space robots primarily utilize rigid structures, resulting in limited degrees of freedom, which restricts their operational capabilities. In contrast, soft robots with greater flexibility and robustness may be used for future space exploration. Soft robots applied in space environments must overcome significant challenges associated with ultrahigh vacuum, microgravity, extreme temperatures, and high‐energy radiation. Herein, a comprehensive analysis of the key advantages of soft robots is presented based on the special requirements of the space environments for soft robots. Furthermore, brief insights into how soft robots must be changed in terms of their design, modeling, fabrication, sensing, and control to adapt to space environments are discussed. Specifically, soft robot scenarios with potential space application value are introduced. Finally, opinions regarding the potential directions of soft space robots are provided. Abstract : The development of space robots is vital to broadening human cognitive boundaries. Compared with rigid space robots with limited degrees of freedom, soft robots exhibit apparent advantages of dexterity, adaptability, and robustness. Successes such as inflatable antennas have attracted interest in soft space mechanisms. Soft robots are expected to have a role in future on‐orbit missions and planetary exploration.